TEORI CONTIGUOUS CONDITIONING EDWIN RAY GUTHRIE DAN PENERAPANNYA DALAM PEMBELAJARAN PAI DI SEKOLAH - Ghulamul Mustofa (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2019)
This article aims to describe the contiguous conditioning theory and its application in Islamic religious education in schools. Contiguous conditioning theory has the meaning of the closeness of conditions that occur based on the relationship between the stimulus and the relevant response. The method used in this research is literature study where the author tries to find, compile and analyze various information through various related sources. The results of this study explain that learning is a process of change that occurs due to conditions which then cause a reaction (response). Some aspects that cannot be separated from this theory are forgetting, punishment, encouragement, intention, and transfer training. Edwin Ray Guthrie came up with three methods that can be used to change habitual behavior, namely the Threshold Method, the Fatigue Method, and the Incompatible Response Method. These three methods can be used by Islamic Education teachers in implementing their learning in the classroom. The positive contribution of this article informs that the contiguous conditioning theory is very suitable to be applied to develop students' abilities both from the cognitive, affective, and psychomotor domains. One way for this theory to work optimally is that the teacher must use interesting learning methods or strategies.